An Enhancement of AODV with Multi-Radio in Hybrid Wireless Mesh Network. (3rd September 2013) - Alrayes, Mohammad Meftah; Biswash, Sanjay Kumar; Tyagi, Neeraj; Tripathi, Rajeev; Misra, Arun Kumar; Jain, Sanjeev
Abstract : AODV-MR (on-demand routing protocol with multi-radio extension) has been designed to support multi-radio interfaces; it uses more than one interface of the same mesh router or gateways for broadcasting duplicated control packets (i.e., RREQ, RRER, and HELLO message) or to rebroadcast it. We have modified AODV-MR, by allocating one interface in a dynamic manner for sending routing/control packets or data packets. This allocation of interfaces is based on type of mesh routers and traffic direction. The efficiency and effectiveness of the modification work have been evaluated compared with AODV-MR in terms of packet delivery ratio, routing packet overhead, end to end delay, and throughput.